2007
DOI: 10.1017/s0021859607007204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uncertainty on the optimum nitrogen fertilization rate and agronomic, ecological and economic factors in an oilseed rape based crop rotation

Abstract: SU MMARYCrop yield and optimum nitrogen fertilization rates (Nopt) are often calculated ex post by specific functions of the nitrogen fertilization rate, but in doing this, uncertainties in terms of model choice, annual nitrogen response variations and parameter estimation are neglected. In the present study, Nopt, grain yields, net revenues and N balances were estimated for the three crops of an oilseed rape (OSR)-winter wheat-winter barley rotation. The effects of uncertainties were considered using three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…The authors suggested reducing the spring N amount if N in the canopy exceeds 50 kg•N•ha −1 at the end of autumn growth. With only small increases in N offtake by the seeds (Table 3) and the resulting small NUE (Table 4) In order to describe the N effects, a "Linear Response and Plateau" approach (LRP) was chosen, since using quadratic N response curves resulted in quite high N amounts required to achieve yield maximum due to a less steep slope compared to wheat [30,31]. Although the quadratic approach Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors suggested reducing the spring N amount if N in the canopy exceeds 50 kg•N•ha −1 at the end of autumn growth. With only small increases in N offtake by the seeds (Table 3) and the resulting small NUE (Table 4) In order to describe the N effects, a "Linear Response and Plateau" approach (LRP) was chosen, since using quadratic N response curves resulted in quite high N amounts required to achieve yield maximum due to a less steep slope compared to wheat [30,31]. Although the quadratic approach Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…In order to describe the N effects, a "Linear Response and Plateau" approach (LRP) was chosen, since using quadratic N response curves resulted in quite high N amounts required to achieve yield maximum due to a less steep slope compared to wheat [30,31]. Although the quadratic approach seems to be safer in terms of preventing financial losses under conditions of uncertainty, the risk of high positive N balances rises and the introduction of penalty functions may therefore favor the LPR model, especially against the background of high N surpluses in WOSR growing systems [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sylvester-Bradley et al (1982) used a second order Taylor series expansion to compute the approximate mean and variance of EONR for an exponential plus linear yield response function, and their approach can be used with other yield functions. In a recent paper, Henke et al (2007) used a Monte Carlo approach to compute confidence bands for the quadratic, quadratic plateau, and linear plateau yield response functions. While this ''brute force'' method is applicable to any response function, it gives exact confidence bands only for functions that are linear in their parameters, such as the quadratic equation.…”
Section: Introductionmentioning
confidence: 99%
“…While this ''brute force'' method is applicable to any response function, it gives exact confidence bands only for functions that are linear in their parameters, such as the quadratic equation. For non-linear functions-functions that depend non-linearly on one or more unknown parameters-the approach by Henke et al (2007) does not give exact confidence bands because the parameter estimates found from least squares regression are not normally distributed or unbiased for data sets with few observations, which is typical of yield response studies. This was clearly illustrated by Hernandez and Mulla (2008), who showed how alternative methodologies for computing confidence bands must be used when computing bands for non-linear equations, such as the non-linear formulation of the quadratic equation that they used.…”
Section: Introductionmentioning
confidence: 99%